METODE KRITIK HADIS ABU HAFS AMR BIN ALI ALFALLAS - Fuad, Samsul (LPPM IAIN Kediri, 2023)
The Sanad is the chain of narrators in a hadith, which serves as the basis for hadith scholars in presenting the content of a hadith. To understand how a narrator's credibility is assessed, knowledge of jarh wa ta'dil is essential. This article elucidates how Abu Hafs Amr bin Ali engages in the criticism (jarh) and accreditation (ta'dil) of hadith narrators, determining the authenticity or weakness of the transmitted hadith. The research utilizes a literature review method and is presented in a descriptive-analytical format. The article also provides a biography of Abu Hafs Amr bin Ali Al Fallas, who was not only a hadith narrator but also a critic of narrators. He was born in Basra in the 160s A.H. and began studying hadith from a young age. Among his teachers were Waqi' and Yahya al-Qattan, and among his students were Imam Bukhari, Imam Muslim, Imam At-Tirmidhi, and others. In critiquing a hadith, Amr bin Ali employs various methods, including expressing jarh wa ta'dil through specifying the attribution of the hadith narrator and conveying the opinions of his teachers